(untitled) (Revista Lusófona de Educação, 2025)
This study aims to analyze differentiated teaching practices for students with Autism Spectrum Disorder (ASD) with a view to promoting school inclusion. The investigation adopted qualitative research as the methodological approach and the case study as the research procedure. With this in mind, the research took place in a 2nd year elementary school class, in a public school in the city of Fortaleza - Ceará - Brazil. More specifically, the research focused on analyzing the differentiated teaching practices aimed at one of the students with ASD, aged 7, who is also diagnosed with Oppositional Defiant Disorder (ODD). As a result, the study showed how mapping the student’s interests, learning profile and level of preparation provides support for differentiating the content, process and producer, as advocated by the differentiated teaching approach, considering the promotion of learning and collaboration with the schooling processes and the inclusion of the student with ASD. As a result, we concluded that differentiated teaching is a viable methodological approach for promoting practices that focus on the schooling process of students with ASD from an inclusive perspective. Keywords: Autism Spectrum Disorder; School Inclusion; Differentiated Teaching.